2015
DOI: 10.1007/s13277-015-4301-6
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long non-coding RNA TUG1 correlates with poor prognosis and disease status in osteosarcoma

Abstract: The pathogenesis of osteosarcoma involves complex genetic and epigenetic factors. This study was to explore the impact and clinical relevance of long non-coding RNA (lncRNA), Taurine up-regulated gene 1 (TUG1) on patients with osteosarcoma. Seventy-six osteosarcoma tissues and matched adjacent normal tissues were included for analysis. The plasma samples were obtained from 29 patients with osteosarcoma at pre-operation and post-operation, 42 at newly diagnosed, 18 who experienced disease progression or relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 35 publications
7
109
0
Order By: Relevance
“…TUG1 was significantly upregulated in ESCC tissues compared with adjacent non-cancerous tissues. This result agrees with the findings of previous studies [14,15,25]. Furthermore, patients with high TUG1 expression showed worse OS, which may explain the high prevalence of chemotherapy resistance in cases with TUG1 overexpression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…TUG1 was significantly upregulated in ESCC tissues compared with adjacent non-cancerous tissues. This result agrees with the findings of previous studies [14,15,25]. Furthermore, patients with high TUG1 expression showed worse OS, which may explain the high prevalence of chemotherapy resistance in cases with TUG1 overexpression.…”
Section: Discussionsupporting
confidence: 92%
“…The normal expression of TUG1 is thus speculated to exert an inhibitory effect on some apoptosis-related genes; that is to say, TUG1 may exert an anti-apoptotic effect similar to that of survivin [12]. Ma et al [15] recently reported that TUG1 expression was upregulated in osteosarcoma, and its high expression leads to poor prognosis and short survival time. Han et al [14] reported upregulation of TUG1 in bladder urothelial carcinoma affecting cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from tissues or serum samples by Trizol reagent (Thermo Fisher Scientific) and Trizol LS reagent (Thermo Fisher Scientific) as described in our previous study 16. cDNA was synthesized using the PrimeScript RT reagent Kit with gDNA Eraser (Takara, Dalian, People’s Republic of China).…”
Section: Methodsmentioning
confidence: 99%
“…Of these, 129 duplicated articles were excluded; through title and abstract review, studies describing unrelated topics (n = 80) which refers to those studies that were not research articles or those studies unrelated to osteosarcoma, lncRNA , or patient prognosis were removed; after reading the remaining 54 full-text articles, studies lacking relevant data (n = 32), studies presented in language other than English (n = 1), fulltext unavailable studies (n = 1), and the studies of which included patients were reported in previous studies (n = 1) were excluded. Eventually, 19 studies (containing 1298 patients) met the inclusion criteria and were evaluated in this analysis [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The screening process and results was shown in Figure 1.…”
Section: Included Studies and Characteristicsmentioning
confidence: 99%